Dynamism of Building Standards & Designs to Private Developers Towards Urban Poor Low-Cost Resettlement Quality of Life: A Review Comparison in Malaysia & Singapore - Hanapi, Nur Amalina; Ridzwan, Nurul Fahmira; Keane, Adrienne (International Journal of Sustainable Construction Engineering and Technology, 2023)
Malaysia’s government adopted many resettlement initiatives and housing policies to eliminate the growing number of informal settlement as well as meet the housing demands and improvement in the quality homes in order to achieve its aim of being a civilized country by 2020. Critical number of studies has been carried to investigate the low-cost dwelling in city centre effect to quality of life of occupants. However, there lack of study comparisons in terms of design and building standards structured being made to our neighbouring country Singapore which more developed in its city planning and shared the same climatic condition as Malaysia. Therefore, this paper aim to investigate the impact of the both dynamism building design and standard for the private developers concerns with regards to low-cost urban settlement. This paper explores the methodology through secondary type of data by articles, guidelines and researches involved with architectural design modifications and intervention programs establishment offered by both countries. This paper then discussed on Malaysian resettlement policy programmes intervention criteria and its nature in interior thermal comfort condition, improper layout plan, exterior design scheme and public amenities provision practiced in improving quality of life of the urban poor resettlements. As the outcome of these findings, this research suggest that Malaysia still have possibilities that could be improved for these dwellings through imposing stringent protocols on building plan, certificate, permit, licences and other documentation by local authorities for each states and Commissioner of Building for the private developers to ensure the upgraded consistency level urban settlements is being maintained.